Manganese(II)-Catalyzed Esterification of N-β-Hydroxyethylamides - Nishii, Yuji; Akiyama, Shoko; Kita, Yusuke; Mashima, Kazushi (Synlett, 2015)
A catalyst system of manganese with 2,2-bipyridine for amide alcoholysis of N-β-hydroxyethylamides is described. This protocol enabled selective cleavage of the amide bond through a mechanism involving sequential N,O-acyl rearrangement and transesterification.
Keywords: amides; esterification; manganese; selective reaction; acyl rearrangement